A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins - Protogino, Lucila C.; Miquelarena, Amalia M.; López, Hugo L. (Zootaxa, 2006)
A new species of Astyanax, which is unusual in having breeding tubercles in mature males, is described from the Paraná and Uruguay river basins. The new species is distinguished from all other members of the genus by this feature, together with the following unique combination of characters: a round or trapezoidal humeral spot; a branch of the infraorbital sensory canal directed ventrally, continued as a series of pores totally or partially traversing the third infraorbital; body relatively slender (31.8–37.4 %SL); eye large (41.1–45.8 %HL); snout short (15.5–20.9 %HL); caudal peduncle relatively slender (10.3–12.0 %SL); maxilla with 1 pentacuspid tooth; 38–42 perforated scales in lateral line and v–vi, 23–29 anal fin rays. Males have dermal contact organs on all fins and epidermal breeding tubercles on the head and scales.